Informational Dashboard untuk Monitoring Sistem Drainase secara Real-Time - Dini Nurmalasari; Retro Tri Wahyuni; Yusmar Palapa (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2015)
Drainage is used to drain excess water, either from rain water or waste water. Currently, management and monitoring of drainage system is still done manually, therefore there are some lacks, for example: monitoring the condition of the drainage can not be performed continuously, requiring enough personnel to monitor all the drainage conditions, the data is not stored properly, and inability to know the condition of drainage quickly. Web-based monitoring application supported by informational dashboard is able to provide data and information on the condition of drainage system effectively and efficiently. The monitoring system is also equipped with map, so users can directly determine the current condition of each monitoring station through a two-dimensional visualization.